Tinjauan Kriminologis terhadap Anak yang Melacurkan Diri (Studi Kasus di Kota Lewoleba, Kabupaten Lembata): Criminological Review of Child Prostitution (Case Study in Lewoleba City, Lembata Regency) - Making, Maria M.F; Wilhelmus, Bhisa V.; Manafe, Deddy R. Ch. (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The increasing number of child prostitutes in Lewoleba City illustrates the still very low level of welfare of the population, which is very concerning, and the lack of attention given by parents and the social environment. This study aims to determine what factors influence children to prostitute themselves, the impacts experienced, and the efforts and obstacles experienced in overcoming the problem of children who prostitute themselves in Lewoleba City. This study uses an empirical approach, namely an approach based on the type of data and data analysis. The research findings show that: (1) Children who prostitute themselves are influenced by family factors, economy, social environment, low levels of education and low self-control. (2) The impacts experienced by children due to prostitution are contracting sexually transmitted diseases such as HIV/AIDS and other infectious diseases, physical damage due to violence, trauma, and being isolated or ostracized by society. (3) Efforts that have been made to overcome this problem include conducting outreach related to women and children in several schools, sub-districts/villages with the Cross-Sector National Commission such as PLAN, KPAD, Health Service and Women and Children Protection Team from each sub-district, issuing coaching programs such as social rehabilitation programs, counselling services, counselling and education related to the dangers of exposure to HIV/AIDS and other infectious diseases, cooperation between the police and law enforcement by conducting raids. Meanwhile, the obstacles experienced are the limitations of the Law or the absence of special rules or regional regulations that regulate in detail children who prostitute themselves, lack of human resources and facilities, difficulties in identifying and approaching victims and the limited role of local government.